Current trend in treatment of glioblastoma in Japan: a national survey using the diagnostic procedure combination database (J-ASPECT study-glioblastoma) - Funakoshi, Yusuke (Int J Clin Oncol, 2021)
BACKGROUND: In the treatment for glioblastoma (GBM), treatment modalities, such as bevacizumab (BEV) and carmustine wafers implants have been approved in Japan since 2013. However, it is unclear whether such a trend in treatment complexity can accelerate treatment centralization. The aim of this study was to reveal the current trend in the treatment of GBM in Japan. METHODS: We used diagnostic procedure combination (DPC) database to analyze the data of 1,774 patients from 305 institutions between April 2016 and March 2019. To analyze the situations associated with first-line BEV use during concurrent TMZ (temozolomide)-radiotherapy, we compared TMZ alone and TMZ–BEV groups. RESULTS: Of the 1,774 patients with GBM, tumor removal by craniotomy was performed in 1,572 (88.6%) patients, and stereotactic biopsy was performed in 156 (8.8%) patients. A total of 1,229 (69.3%) patients underwent radiotherapy, and 1,287 (72.5%) patients underwent chemotherapy. TMZ alone was administered to 878 (68.2%) and TMZ combined with BEV in 381 (29.6%) patients. In the TMZ–BEV group, as compared to the TMZ-alone group, the rate of discharge to home was significantly lower (P = 0.0044), and the rate of stereotactic biopsy was significantly higher (P < 0.0001). No significant difference was observed in the distribution of patients between the TMZ alone and TMZ–BEV groups depending on the scale of institution (P = 0.1240). CONCLUSION: First-line BEV administration seems to be selected properly regardless of the institutional scale. This Japan-wide study of GBM treatment revealed that high level and newly introduced treatments have been steadily generalized in Japanese institutions.